2015
DOI: 10.1136/bmjopen-2014-006379
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of driving fitness in patients with visual impairment to understand the elevated risk of motor vehicle accidents

Abstract: ObjectiveTo assess the driving fitness of patients with glaucoma by identifying specific areas and degrees of visual field impairment that threaten safe driving.DesignCase–control study.Setting, and participantsThis prospective study included 36 patients with advanced glaucoma, defined as Humphrey field analyzer (HFA; 24-2 SITA standard program) measurements of mean deviation in both eyes of worse than −12 dB, and 36 age-matched and driving exposure time-matched normal subjects. All participants underwent test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 36 publications
1
40
0
1
Order By: Relevance
“…54 We certainly need better evidence-based tests for determining those patients who are fit to drive and this might be determined by a variety of methods using driving simulators and collision data. [55][56][57][58] Other vision-related tasks also seem to be inhibited by glaucomatous visual field loss. The lighting conditions under which tasks are performed may be even more important that the task itself and this warrants further research.…”
Section: Aspects Of Visual Disability In Glaucomamentioning
confidence: 99%
“…54 We certainly need better evidence-based tests for determining those patients who are fit to drive and this might be determined by a variety of methods using driving simulators and collision data. [55][56][57][58] Other vision-related tasks also seem to be inhibited by glaucomatous visual field loss. The lighting conditions under which tasks are performed may be even more important that the task itself and this warrants further research.…”
Section: Aspects Of Visual Disability In Glaucomamentioning
confidence: 99%
“…A study by the same research group that included a larger sample of glaucoma patients with a wider range of field loss, showed that the drivers with glaucoma had more self‐reported and simulator crashes than controls and these were significantly related to the extent of the peripheral visual field. Similarly, a recent case‐controlled study reported that patients with advanced glaucoma (mean defect worse than ‐12 dB in both eyes) had significantly more simulator crashes in some driving scenarios, which were related to integrated visual field sensitivity; however, the drivers were not required to operate the steering wheel or the brake. In another small scale simulator study, drivers with glaucoma made more steering actions and were worse on a detection task than controls but there were no other between group differences; however, it should be noted, that there was no possibility of compensating for visual impairment in this study by reducing driving speeds as speed was fixed.…”
Section: Glaucomamentioning
confidence: 89%
“…Many studies have suggested a significant relationship between the deterioration in patients' VAs (and/or their VF) and driving ability. 2837 However most of these studies assessed driving ability in an artificial situation. 28,37–41 For example, Crabb et al 39 investigated eye movements during a PC-based driving simulation and suggested that superior VF damage is disadvantageous for driving ability.…”
Section: Discussionmentioning
confidence: 99%
“…Tatham et al 37 investigated the relationship between MVCs in drivers with glaucoma and visual function, and found that the reaction times to low contrast divided attention tasks during driving simulation were significantly associated with a history of MVC. Kunimatsu et al 28 reported that patients with advanced glaucoma were involved in a significantly higher number of collisions in a driving simulator than controls. Szylk et al 40 reported that the number of accidents, measured in a driving simulator, in a glaucoma group was correlated significantly with peripheral VF extent.…”
Section: Discussionmentioning
confidence: 99%